2006
DOI: 10.1188/06.cjon.503-508
|View full text |Cite
|
Sign up to set email alerts
|

Couples Surviving Prostate Cancer: Long-Term Intimacy Needs and Concerns Following Treatment

Abstract: Couples surviving prostate cancer face long-term challenges in their relationships as they adapt to chronic illness. Ten couples surviving prostate cancer were brought together in a focus group to discuss their experiences and concerns regarding intimacy in their relationships. During three 30-minute segments, couples described their experiences (a) as couples, (b) as individual men and women in two concurrent break-out groups, and (c) regarding current intimacy and relationship needs. Questions asked of coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 36 publications
1
107
0
2
Order By: Relevance
“…[56][57][58][59] The factors that cause distress in partners are patients' physical pain and physical limitations. 53,58,60 Some partners are distressed by men's urinary incontinence. 53 Couple relationships are affected by prostate cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58][59] The factors that cause distress in partners are patients' physical pain and physical limitations. 53,58,60 Some partners are distressed by men's urinary incontinence. 53 Couple relationships are affected by prostate cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Communication within the couple is reported as an area of difficulty because couples often do not share their concerns; men and women report different needs for intimacy and guidance about recovery from treatment. 42,[60][61][62] The trajectory of coping may be different for patients and partners. Couper et al 63 found in a sample of 103 survivors and 103 partners that partners' rates of depression, distress and anxiety (per criteria Diagnostic and Statistical Manual of Mental Disorders 4th edition) were higher than those of the patients and the general Australian population.…”
Section: Resultsmentioning
confidence: 99%
“…Además, las mujeres de los pacientes pueden llegar a presentar mayor malestar emocional que los propios pacientes (59,60) , manifestando tener carencia de información e incertidumbre sobre el futuro (60)(61)(62) , menor percepción de autoeficacia y menos apoyo social y de recur-sos (60) . Las dificultades principales que se presentan en la relación de pareja son la comunicación, la sexualidad y la intimidad (63,64) . A la hora de elaborar programas e intervenciones en los pacientes con cáncer de próstata y sus supervivientes, es necesario tener en cuenta los cambios que se producen en las áreas físicas, psicológicas y sociales, haciendo intervenciones lo más específicas posibles a la situación.…”
Section: Aspectos Psicológicosunclassified
“…Les difficultés signalées par les partenaires comprennent la détresse liée à l'inquiétude et à les tensions liées au rôle (Harden, 2005), le manque d'information (Butler et coll., 2000), les difficultés liées à l'intimité et à la sexualité (Couper et coll., 2006;Crowe & Costello, 2003;Sanders, Pedro, Bantum & Galbraith, 2006) et les enjeux de communication avec le partenaire malade (Boehmer & Clark, 2001b;Hawes et coll., 2006;Lavery & Clarke, 1999). Le stade de la maladie est rarement cerné dans les études sur les partenaires d'hommes ayant le cancer de la prostate (Crowe & Costello, 2003;Feltwell & Rees, 2004;Harden, Northouse & Mood, 2006;Manne, Babb, Pinover, Horwitz & Ebbert, 2004;Rees et coll., 2003 Besoins similaires des proches des hommes ayant un cancer de la prostate HS et de ceux ayant un cancer de la prostate AI…”
Section: Cette éTude Exploratoire a Dégagé Les Besoins En Matière De unclassified